Pelaksanaan Program Pembangunan Taman Wisata di Desa Unamendaa - Arafat, Arafat; Syahrir, Sasmita Nabila; Triani, Neks (SIGn Journal of Social Science, 2022)
This research aims to explore and describe the implementation of the tourism park development program in Unamendaa Village. This research uses an inductive qualitative analysis. Inductive analysis is an approach that begins with field facts, analyzes them based on relevant theories and arguments, and ultimately yields a conclusion. The results show that implementing the Tourism Park development program in Unamendaa Village faces several significant obstacles related to communication, resources, disposition, and bureaucratic structure. Regarding communication, the Village Tourism Park program’s socialization needs to be implemented optimally. Regarding resources, there needs to be more BUMDes Organizers in managing the Village Tourism Park. Concerning disposition, although the Village Government has entrusted development responsibility to BUMDes, there still needs to be clarity in the tax payment mechanism. Additionally, the suboptimal bureaucratic structure adds complexity to the obstacles, including issues of supervision, coordination, facility provision, and communication between the Village Government and the community, which collectively hinder the achievement of the Village Tourism Park development goals. Therefore, it is recommended that the Village Government improve communication effectiveness with the community through increased frequency and more innovative socialization methods to ensure that information about the Village Tourism Park development is evenly distributed to all community members. For BUMDes, it is suggested that resource deficiencies be addressed by training organizers in tourism park management and operations and clarifying the division of responsibilities between organizers and traders to prevent role overlaps. Traders are expected to cooperate more closely with BUMDes Organizers, especially regarding compliance with the established tax payment mechanism. The community is encouraged to actively participate in every process of the Village Tourism Park development, in aspects of planning, execution, and supervision, to create good collaboration between the Village Government, BUMDes, traders, and the community, aiming for the sustainable and beneficial development of the Village Tourism Park for all parties in the future.